Penerapan Teori Penetrasi Sosial dalam Analisis Komunikasi Interpersonal Keluarga Non-Biologis pada Family by Choice - Putri , Cindyka Ardelia; Ike Desi Florina; Sarwo Edy (Universitas Muhammadiyah Prof. DR. Hamka, 2025)
This research aims to analyze the dynamics of interpersonal communication within non-biological families through the Korean drama